HUBUNGAN INOVASI, KOMITMEN DAN MOTIVASI KERJA DENGAN PROFESIONALISME WIDYAISWARA PADA PUSAT PENGEMBANGAN DAN PEMBERDAYAAN PENDIDIK DAN TENAGA KEPENDIDIKAN MEDAN - HSB, Irwan; Zainuddin, Zainuddin; Sinaga, Anton AP (LPPM Universitas Darma Agung, 2020)
Professionalism is a description of the degree or level of knowledge and expertise and attitudes that are also owned by a person to be able to perform tasks in accordance with his profession or position. The efforts made by PPPPTK Medan to improve the professionalism of the “widyaiswara” have not been fully successful, because there are still many scholars who are less able to plan and carry out the learning process properly. “Widyaiswara” also lacks commitment and is not motivated to develop the learning process as demanded by his profession as a teacher of the Education and Training. This research aims at finding the relationship between innovation, commitment and work motivation either partially or simultaneously with the professionalism of the “widyaiswara” at the Center for Development and Empowerment of Educators and Educational Personnel in Medan. The population of this research is 53 “widyaiswara” people. To determine the number of samples saturated samples are used so that the sample amounted to 53 people. Data collection techniques in this study were questionnaires, interviews and documentation studies. While the data analysis technique used is the classical assumption test, correlation analysis and the coefficient of determination. The results show that the innovation variable has a positive and significant relationship with the professionalism of “widyaiswara” in PPPPTK Medan with a correlation coefficient of 0.885, which means that the level of the relationship is very strong. The commitment variable has a positive and significant relationship with the professionalism of the “widyaiswara” in PPPPTK Medan with a correlation coefficient of 0.875, which means that the level of the relationship is very strong. The work motivation variable has a positive and significant relationship with the professionalism of the widyaiswara at PPPPTK Medan with a correlation coefficient value of 0.899 which has a very strong level of relationship. The variables of innovation, commitment and work motivation simultaneously have a significant relationship with the professionalism of the “widyaiswara” at PPPPTK Medan. The coefficient of determination is 85.90%, the variation of professionalism can be explained by innovation, commitment, and work motivation, while the remaining 14.10% is explained by other factors, such as compensation and work environment variables. It is suggested that “Widyaiswara” needs to increase his innovation by looking for new things in learning, as well as innovating to overcome difficulties in the delivery of learning. “Widyaiswara” needs to improve his commitment to the education and training agency by feeling the problems that occur in the institution are also a problem, and feels it is important to complete the tasks that have been delegated to him to achieve the objectives of the education and training agency. “Widyaiswara” at the institution should have the opportunity to increase their abilities through education and training, and receive appropriate awards according to their work performance. It is necessary to do further research on other independent variables such as compensation and work environment to see its relationship with “widyaiswara's professionalism.